Manajemen Kesiswaan dalam Upaya Meningkatkan Prestasi Akademik dan Non Akademik Peserta Didik - Daniatun Khasanah; Danang Dwi Prasetyo (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2023)
Every educational institution must have different student management which is unique or rare between one educational institution and another. This study is a literature review that explores and analyzes the results of various types of previous research on related topics. This research seeks to explain the results of student management studies with the aim of increasing student achievement. Based on the results of this literature review, we can conclude that : (1) student programs are planned at the beginning of the school year and approved by the principal, teachers and supervisors. (2) The implementation of student management has several stages, including: Acceptance of new students, Selection of students, Orientation of students, Placement of students, Guidance and development of students. (3) Evaluation is carried out based on each field by supervisors who are expert in their fields. Evaluation is able to find out the comparison of targets with achievements, as well as knowing the inhibiting and supporting factors.